Cloud Business Process Management Model (CBPMM): Process of BPM as a Service (PoBPMaaS) - Tomasz GZIK (Communications of International Proceedings, 2021)
The ongoing information revolution and the experiences of 2020 related to the COVID-19 pandemic show that companies wishing to maintain business continuity and remain competitive in a dynamically changing environment, absolutely must have the ability to properly assess the current market situation, forecast the future and quickly, effectively and efficiently adapting business processes. Business Process Management - as one of the dynamically developing disciplines of management and Cloud Computing - as a strategic direction of the evolution of IT solutions, together create business, management and technical potential for enterprises, as well as constitute an interesting area of ​​scientific research. In the traditional model, Business Processes Management in Cloud Computing is performed with the support of services that correspond to the functionalities of Business Process Management System – Business Process Management System as a Service (BPMSaaS). Other possibilities, focused on outsourcing business processes, are provided by Business Process as a Service (BPaaS). Literature and numerous studies show that despite IT capabilities, enterprises have a problem with managing business processes. The sources of these problems are seen among others in competences, the lack of a methodical approach, the dynamics of the company and its environment. Market trends and forecasts of analytical companies indicate that in the coming years companies will increasingly outsource business processes using BPaaS services. There are discrepancies in the terminology associated with managing business processes in cloud. There is also a lack of comprehensive guidance how to manage processes using Cloud Computing. This state of affairs was a motivation for the Author to develop the concept of a Business Process Management Model in Cloud Computing – Cloud Business Process Management Model (CBPMM). CBPMM takes into account various perspectives and elements of process management, in particular organizes terminology, introduces new terms and presents the concept of a new type of service - Process of Business Process Management as a Service (PoBPMaaS). The aim of the article is to present and explain the basic issues and potential related to BPM in Cloud Computing. Article also presents the new concept of Cloud Business Process Management Model (CBPMM) and cloud service Process of Business Process Management as a Service (PoBPMaaS).
Keywords: Business Process Management; Cloud Computing; Business Process Management in Cloud Computing; Cloud Business Process Management Model; Process of Business Process Management as a Service